2023
DOI: 10.1080/21645515.2023.2269790
|View full text |Cite
|
Sign up to set email alerts
|

AIM2 fosters lung adenocarcinoma immune escape by modulating PD-L1 expression in tumor-associated macrophages via JAK/STAT3

Hua Ye,
Wenwen Yu,
Yunlei Li
et al.

Abstract: This work was devised to discuss the effect of AIM2 on the immunosuppression of LUAD tumors, as well as its molecular mechanism. An allograft mouse model was built. Mouse macrophages were isolated and collected. The infiltration level of Mø and expression of M1 Mø, M2 Mø markers, and PD-L1 were assayed by IHC and flow cytometry. Expression levels of M1 Mø and M2 Mø marker genes and PD-L1 were detected by qPCR. The expression of proteins linked with JAK/STAT3 was tested by western blot. CD8 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Mitogen-activated protein kinase 3 (MAPK3) is activated by multiple stimuli [ 22 ]. MAPK3 and related downstream signaling pathways have been shown to be important regulators of OP progression [ 23 , 24 ]. Wang et al reported that Novel Soy Peptide CBP promotes osteoblast differentiation in OP through activation of the MAPK pathway [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitogen-activated protein kinase 3 (MAPK3) is activated by multiple stimuli [ 22 ]. MAPK3 and related downstream signaling pathways have been shown to be important regulators of OP progression [ 23 , 24 ]. Wang et al reported that Novel Soy Peptide CBP promotes osteoblast differentiation in OP through activation of the MAPK pathway [ 25 ].…”
Section: Introductionmentioning
confidence: 99%